Training on election process dispute resolution between participants in Baubau City - Eko Satria; Zubair Zubair; Harry Fajar Maulana; Andi Bangsawan Makaraeng Elhaq; Rangga Adwian (Universitas Muhammadiyah Magelang, 2024)
Bawaslu has been granted the authority to resolve disputes that arise among participants through PerBawaslu Number 9 of 2022, which concerns Procedures for Resolving General Election Process Disputes. Panwascam will play a crucial role in resolving election process disputes, particularly those between election participants. The aim of this activity is to ensure the effectiveness of Panwascam in resolving disputes, maintaining election integrity, and building public trust in the democratic system in Baubau City. The method used in this service involves providing material through technical work meetings. The technical working meeting for implementing dispute resolution during the 2024 general election campaign process resulted in increased understanding for Panwascam in resolving election disputes, especially those between election participants. This includes enhancing the capacity of Panwascam members, ensuring their independence from political intervention, and facilitating a quick resolution of election disputes through collaborative efforts with relevant stakeholders such as community leaders.